Post-Operative Radiotherapy of the Rhabdomyosarcoma R1H of the Rat. (1997) - Carl, Ulrich M.; Sminia, Peter; Bahnsen, Jens; Fröschle, Günter; Omniczynski, Maria; Wolf, Lothar; Krüger, Uwe; Hartmann, K. Axel; Beck-Bornholdt, Hans-Peter
Abstract : Purpose . Post-operative radiotherapy (RT) is routinely applied in the treatment of several human tumours. The aim of the present study was to investigate the value of post-operative RT in a rat model. Methods . Experiments were performed using the rhabdomyosarcoma R1H of the WAG/Rij rat. Animals were randomized to different treatment schedules: surgery, RT or a combination of both. Tumours were excised at different sizes (0.1–4.5 g) aiming for complete macroscopic resection. RT (60 Gy in 30 daily fractions over 6 weeks) was applied either primarily or to the former turnout site from the third post-operative day. Tumour growth delay, time to recurrence and local tumour control were used as endpoints. Results . Pre-operative tumour size determined the time and rate of recurrence. The larger the tumour, the shorter the time to relapse and the higher the recurrence rate. The 50% local control rate (LCR 50 ) for surgery was found in tumours with a mass of 0.8 g. For post-operative RT a LCR 50 was achieved for tumours with a mass of 1.1 g. For larger turnouts (> 1.1 g), however, the rate and time course of relapse were similar for both the group receiving RT alone and the group receiving post-operative RT. Discussion . In this model the tumour mass at excision governs the prognosis. Relatively small R1H turnouts may recur despite complete macroscopical resection. With regard to the LCR, the outcome for larger tumours is improved with post-operative RT (60 Gy/6 weeks) than compared with surgery alone. The factor is 1.3. Within a certain range of tumour sizes, combined treatment (surgery + RT) can improve the outcome considerably.